Preliminary results on microplastics in surface water from the downstream of the Day River - Doan Thi, Oanh; Duong Thi, Thuy; Nguyen Thi Nhu, Huong; Hoang Thi, Quynh; Le Thi Phuong, Quynh; Duong Hong, Phu; Le Phuong, Thu; Bui Huyen, Thuong (Vietnam Journal of Earth Sciences, 2021)
Microplastics (MPs), referring to plastic items ranging from 1 to 5000 µm long, are polluting the terrestrial and aquatic environments and are becoming a threat to the health of ecosystems, biota, and humans. Rivers are major carriers of these materials from the terrestrial environment to the oceans. In the present study, the occurrence of MPs in a peri-urban river was investigated. The Day river system is a good example of a peri-urban river strongly influenced by human activities in the whole basin. Water samples were collected from the downstream of the Day river, including Cau Que, Cau Do, and Do Thong, in the rainy and dry seasons using a plankton sampling net for identifying microplastic concentration, size, shape, color, and polymer composition. Microplastic abundance in the surface water ranged from 269,693±60,624 to 863,005±131,925 items/m3. The microplastic concentration in the rainy season was higher than that in the dry season. MPs abundance was increased at a site near urban areas with high human activity. The microplastic shape was collected in different seasons did not change significantly, with microplastic fibers as the major items, accounting for above 92% of the total items. Many fibers microplastics collected in this study were in small sizes of 300-1000 µm and 1000-2000 µm, occupying 78.5-85.7% of the total microplastic items. Purple was the most common color of microplastics. Polyethylene (PE) and polypropylene (PP) were major polymer types of the selected items in the surface water samples downstream of the Day River.